Budaya organisasi, gaya kepemimpinan dan kompensasi terhadap kinerja pegawai melalui kepuasan kerja - Leonardo Martua Sinaga (Lembaga Pengembangan Manajemen dan Publikasi Imperium, 2021)
This study aims to examine the effect of organizational culture and leadership on satisfaction and performance and place compensation as a control variable. Data were obtained through questionnaires, and hypotheses were tested by path analysis. The analysis results support the proposed hypothesis that organizational culture positively and significantly affects job satisfaction and performance. Similar results were also obtained where leadership significantly affected job satisfaction and employee performance. Finally, job satisfaction in this study was shown to predict performance directly and act as a mediator of the relationship between organizational culture and leadership on employee performance.